Screening for swainsonine among South American Astragalus species - Cook, Daniel (2017)
Swainsonine is a toxic alkaloid found in several plant genera worldwide. The objective of this study was to screen several South American Astragalus species for the toxin swainsonine. Swainsonine was detected in 16 of 30 Astragalus species using liquid and gas chromatography coupled with mass spectrometry. Information in regard to the swainsonine content of these species may provide important information on the risk of grazing these toxic species.